Liquid Organic Spent Solvents Co-processing in Cement Industries - Balakrishna, G; Pervez, Shamsh (International Journal of Alternative Fuels and Energy, 2018)
The components and quantities of hazardous waste emissions have been reported to be the pollution indicator of large urban areas. The multiplicity and complexity of sources of pollutants in environment has put forward the need of use alternate fuels in industrial co-processing. The present study is focused on utilization of liquid organic spent solvents (which is hazardous waste produced by the pharma industries) co-processing in cement industries. Specific liquid organic solvents have been selected based on their calorific value and availability for co-processing in Cement industry. Co-processing has been performed by mixing with coal. It has been observed that there is no specific adverse effect on production in comparison with the industries where co-processing is not performing.